Analisis Kinerja Saham Syariah Indonesia dan Malaysia Periode 2011-2018 - Mohammad Farhan Qudratullah (Jurnal Ilmiah Ekonomi Islam, 2022)
Indonesia and Malaysia are two countries in Southeast Asia that are always included in the top ten countries in the world that have the health and development of Islamic Finance according to the State of The Global Islamic Economy (GEI) Report. This study analyzes the performance of Indonesian sharia stocks that are incorporated in the Jakarta Islamic Index (JII) and Malaysian Islamic stocks that are incorporated in the FTSE Bursa Malaysia Hijrah Shariah Index (FHSI) for the period 2011-2018 with a technical analysis approach using 4 indicators, namely: return, volatility, Value at Risk (VaR), and Modified Sharpe Ratio (MSR). The results obtained from this study are that there have no significant differences in return and MSR performance between Indonesian and Malaysian Islamic stocks, but there have differences in volatility and VaR, where Indonesian Islamic stocks have higher volatility and VaR than Malaysia at a 95% confidence level.